Neutrophil Recruitment and Articular Hyperalgesia in Antigen‐Induced Arthritis are Modulated by the Cholinergic Anti‐Inflammatory Pathway. Issue 5 (20th May 2016) - Kanashiro, Alexandre; Talbot, Jhimmy; Peres, Raphael S.; Pinto, Larissa G.; Bassi, Gabriel S.; Cunha, Thiago M.; Cunha, Fernando Q.
Abstract: The cholinergic anti‐inflammatory pathway (CAP) is a complex neuroimmune mechanism triggered by the central nervous system to regulate peripheral inflammatory responses. Understanding the role of CAP in the pathogenesis of rheumatoid arthritis (RA) could help develop new therapeutic strategies for this disease. Therefore, we investigated the participation of this neuroimmune pathway on the progression of experimental arthritis. Using antigen‐induced arthritis (AIA) model, we investigated in mice the effects of vagotomy or the pharmacological treatments with hexamethonium (peripheral nicotinic receptor antagonist), methylatropine (peripheral muscarinic receptor antagonist) or neostigmine (peripheral acetylcholinesterase inhibitor) on AIA progression. Unilateral cervical vagotomy was performed 1 week before the immunization protocol with methylated bovine serum albumin (mBSA), while drug administration was conducted during the period of immunization. On day 21, 6 hr after the challenge with mBSA injection in the femur–tibial joint, the local neutrophil migration and articular mechanical hyperalgesia were assessed. Herein, we observed that vagotomy or blockade of peripheral nicotinic (but not muscarinic) receptors exacerbated the clinical parameters of this disease. Moreover, peripheral acetylcholinesterase inhibition by neostigmine treatment promoted a reduction of neutrophil recruitment in the knee joint and articular hyperalgesia. Our results demonstrated that peripheral activation of CAP modulates experimental arthritis, providing a pre‐clinical evidence of a potential therapeutic strategy for RA.